Dysregulated Immune Profiles for Skin and Dendritic Cells Are Associated with Increased Host Susceptibility to Haemophilus ducreyi Infection in Human Volunteers - Humphreys, Tricia L. (American Society for Microbiology (ASM), 2007)
In experimentally infected human volunteers, the cutaneous immune response to Haemophilus ducreyi is orchestrated by serum, polymorphonuclear leukocytes, macrophages, T cells, and myeloid dendritic cells (DC). This response either leads to spontaneous resolution of infection or progresses to pustule formation, which is associated with the failure of phagocytes to ingest the organism and the presence of Th1 and regulatory T cells. In volunteers who are challenged twice, some subjects form at least one pustule twice (PP group), while others have all inoculated sites resolve twice (RR group). Here, we infected PP and RR subjects with H. ducreyi and used microarrays to profile gene expression in infected and wounded skin. The PP and RR groups shared a core response to H. ducreyi. Additional transcripts that signified effective immune function were differentially expressed in RR infected sites, while those that signified a hyperinflammatory, dysregulated response were differentially expressed in PP infected sites. To examine whether DC drove these responses, we profiled gene expression in H. ducreyi-infected and uninfected monocyte-derived DC. Both groups had a common response that was typical of a type 1 DC (DC1) response. RR DC exclusively expressed many additional transcripts indicative of DC1. PP DC exclusively expressed differentially regulated transcripts characteristic of DC1 and regulatory DC. The data suggest that DC from the PP and RR groups respond differentially to H. ducreyi. PP DC may promote a dysregulated T-cell response that contributes to phagocytic failure, while RR DC may promote a Th1 response that facilitates bacterial clearance.